Advances in electrical stimulation for wound healing - Bi, Xiaofei; Chen, Xiangchen; Pang, Zheng; Song, Bihan; Li, Hongxiang; Feng, Sicheng; Jiang, Hehe; Zhang, Linlin; Hu, Haixiao (Frontiers in Bioengineering and Biotechnology, 2025)
Electrical stimulation (ES), as a cutting-edge biomedical strategy for promoting wound healing, accelerates tissue regeneration and repair processes through directional electric field intervention. Research demonstrates that both endogenous weak bioelectric potentials and exogenously applied electric fields can effectively guide cellular migration along electric field gradients while activating the biological activities of fibroblasts, keratinocytes, and endothelial cells. These mechanisms enhance collagen synthesis and accelerate angiogenesis, thereby significantly improving wound closure rates. This review comprehensively examines recent advancements in ES technology for wound healing, focusing on emerging applications of active microcurrent devices, passive microcurrent systems, and electroactive wound dressings. Particular emphasis is placed on innovative applications of conductive polymers (CPs) and nanocomposite materials in wound repair. By systematically analyzing the underlying mechanisms and therapeutic applications of ES in wound healing, this work aims to provide novel perspectives for optimizing ES technologies and facilitating their clinical translation, offering both theoretical significance and practical value in regenerative medicine.